2020
DOI: 10.1177/1753425920942580
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of NK cells to HBsAg seroconversion in inactive HBsAg carriers following pegylated IFN therapy

Abstract: Our recent study showed a high rate of HBsAg seroconversion in inactive HBsAg carriers (IHCs) treated with pegylated IFN (PEG-IFN). To understand the immune-mediated component of the HBsAg seroconversion better, this study investigated the role of NK cells. A total of 44 IHCs were given 48 wk of PEG-IFN. Fifteen cases achieved HBsAg seroconversion (R group), whereas 29 failed (NR group). The proportion and activity (CD107α and IFN-γ production) of NK cells were measured before and during treatment. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…NKp46, as the activating receptor of NK cells, may regulate the activity of NK cells in the suppression of HBV replication and HBV-related liver injury, meanwhile, it is crucial for the activation of NK cells in chronic HBV infection (42). Our resluts showed that after therapy, the frequency of NKp46 high NK cells and surface reporters IFNAR2 and NKp46 expression on NK cells in patients with HBsAg loss significantly increased, which was consist with some studies suggesting that in patient with CHB, the expression of IFNAR2 and NKp46 on the surface of NK cells elevated after PEG-IFN therapy (32,33), NKp46 high NK cells may be closely correlated to HBV clearance, and up-regulated expression of NKp46 high is beneficial to the clearance of HBV.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…NKp46, as the activating receptor of NK cells, may regulate the activity of NK cells in the suppression of HBV replication and HBV-related liver injury, meanwhile, it is crucial for the activation of NK cells in chronic HBV infection (42). Our resluts showed that after therapy, the frequency of NKp46 high NK cells and surface reporters IFNAR2 and NKp46 expression on NK cells in patients with HBsAg loss significantly increased, which was consist with some studies suggesting that in patient with CHB, the expression of IFNAR2 and NKp46 on the surface of NK cells elevated after PEG-IFN therapy (32,33), NKp46 high NK cells may be closely correlated to HBV clearance, and up-regulated expression of NKp46 high is beneficial to the clearance of HBV.…”
Section: Discussionsupporting
confidence: 82%
“…In a variety of treatment methods for CHB, PEG-IFN has antiviral role and immunomodulatory effect. Previous studies have shown that PEG-IFN therapy can enhance function of NK cells and facilitate virus clearance ( 13 , 31 33 ). NK cells were the important part of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NK cell activity had an increase in patients with HBsAg seroconversion group, especially before the seroconversion of HBsAg, which were not seen in patients without HBsAg seroconversion. In summary, PegIFNα induced NK cells to increase with enhanced activity, which is conducive to the HBsAg seroconversion of IHCs ( 77 ).…”
Section: Chb Functional Cure and Host Immune Responsementioning
confidence: 99%